The Effect Of Organizational Culture And Organizational Commitments On The Performance Of The State Civil Apparatus At The Transportation Office Of Kaur Regency - Tri Wahyudi; Karona Cahya Susena; Zahrah Indah Ferina (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2021)
The purpose of this study was to determine the effect of organizational culture and commitment on the performance of the State Civil Servants at the Transportation Agency of Kaur Regency. The sample in this study was 33 employees at the Transportation Agency of Kaur Regency. The sampling method was by census. Overall, the t test results have a significant value smaller than 0.05, so it means that X1 (organizational culture) and X2 (organizational commitment) have a significant effect on performance (Y) partially or simoultan.